ANALISIS ADOPSI INOVASI PETANI TERHADAP PENGGUNAAN BENIH PADI HIBRIDA DI DESA SUKOREJO KECAMATAN SUKOREJO KABUPATEN PONOROGO - Irfan Sanusi; Masyhuri Mahfudz; Bambang Siswadi (Program Studi Agribisnis, 2019)
ABSTRACTThe way government is going to repair to special harves in ponorogo is by giving the innovation of the hybrid seed. This is the concept of tang development done and spearheaded by the agricultural research center (BPTP) in East Java. But farmers are still reluctant to aplly these new inovations. The study was intented it know the difference in revenue between the farm farmers and the inbred farm farmers and to figure out the aconimic social factor the effected farmers adopt the innovation if paddy sheed hybrid using a logic model analysis. The activity is done in the village of Sukorejo with a sampling of the simple random sampling method of interviewing 50 responders. Being a social economic in the education, the income and frequency following the elightened ones are an influential factor to the farmers in the process of adopting innovation of the hybrid seed. The farmers who adopt the seeds of the new hybrid to continue increases in the effort to increase the production of grain that will eventually improve farmers income.Key words: Paddy, adoption